Search with dynamic working context in software development - Goh, Jeramie Wei Li (2015)
Purpose of this project was to create a search engine webpage using ASP.net with Visual studio Professional and a database using SQL server 2008 express to provide users with relevant results to their search queries. With the help of a search agent, it will be able to filter data store in the Database using SQL query statement in order to retrieve the closest and relevant information to the users. As creating a website is new to me and I have no prior experience, there are lots of researches to be done in order for the project to progress. First would be the design of the User Interface for the website, creating a Database and communication process that was used to link the Database with the web page to generate relevant result for the user queries. This report will also elaborate the limitation that was found during the implementation phase and the future improvement that was required to make the search agent efficient.